Metaphors we rap by: performatividade, estética e política do cotidiano - Silva, Thiago Cazarim da (2019)
This dissertation is a philosophical essay on an issue related to musical productions, speeches and practices that do not have rap as their raison d'être. It is what I call rap's performative claim – the idea that it is a musical genre endowed with different “powers of doing”. However, if this performativity assumes for artists, cultural actors and rap-related fans positive features – such as the power to transform reality, to become socially aware or to turn rap music an instrument of struggle – it is also through a performative claim that state officials and media speeches often harness to rap music a power to incite crime and public disorder, to uphold the structuring values of peaceful social coexistence and even the physical integrity of an individual. Thus, a formation of performative metaphorical chains seems to be central to the appreciation, acceptance, rejection and, eventually, sociocultural and ecological assimilation of such music genre. This essay tries to think over the impact, the need, and the risks encompassed in rap’s performative metaphorization as music genre, in which aesthetics and politics articulate and stress the boundaries between everyday life and fiction.